2018
DOI: 10.2166/wst.2018.060
|View full text |Cite
|
Sign up to set email alerts
|

On the sensitivity of geospatial low impact development locations to the centralized sewer network

Abstract: In the future, infrastructure systems will have to become smarter, more sustainable, and more resilient requiring new methods of urban infrastructure design. In the field of urban drainage, green infrastructure is a promising design concept with proven benefits to runoff reduction, stormwater retention, pollution removal, and/or the creation of attractive living spaces. Such 'near-nature' concepts are usually distributed over the catchment area in small scale units. In many cases, these above-ground structures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…2. Scenarios type 2, in a similar way to the critical component analysis described by Johansson & Hassel [22] and the sensitivity analysis used by Zischg et al [20], an exhaustive exploration of the system state is performed to estimate the consequences of green infrastructures in the sewer system. The idea behind this is to identify strategic locations that produce the largest or most relevant consequences in the network, allowing the identification of the spatial criticalities in terms of resilience improvement for the sewer system's function.…”
Section: Gi Scenariosmentioning
confidence: 99%
See 1 more Smart Citation
“…2. Scenarios type 2, in a similar way to the critical component analysis described by Johansson & Hassel [22] and the sensitivity analysis used by Zischg et al [20], an exhaustive exploration of the system state is performed to estimate the consequences of green infrastructures in the sewer system. The idea behind this is to identify strategic locations that produce the largest or most relevant consequences in the network, allowing the identification of the spatial criticalities in terms of resilience improvement for the sewer system's function.…”
Section: Gi Scenariosmentioning
confidence: 99%
“…This tool was later integrated by Bach et al [19] in the UrbanBEATS model, which integrates stormwater management with urban planning to support the implementation of WSUD. In a simpler manner and focusing on local effects in the network, Zischg et al [20] generated maps which allowed the identification of effective placements for green infrastructure. However, although the placement in the network was considered key in their studies, the implications on resilience and spatial interactions in the sewer systems were not reported.…”
Section: Introductionmentioning
confidence: 99%
“…Together with the characteristics of the rainfall event(s), the relevance of other elements pertaining to the description of the urban catchment and to the infiltration facilities has been investigated (Todeschini et al, 2012;Zischg et al, 2018;Mei et al, 2018;Zeng et al, 2019;Yao et al, 2020). Impacts of climate change and increasing urbanization have also been considered while assessing the behavior of LID practices based on infiltration structures in urban catchments (e.g., Saurav et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Low impact development (LID), also known as green infrastructure (GI), controls runoff and nonpoint source pollution via dispersive interception, storage, and infiltration. Previous studies have shown that LID can alleviate urban waterlogging, regulate runoff, and delay peak runoff, reducing sediment wash-off in the pipeline, and ultimately reducing WWDP. In 2013, sponge cities were proposed in China for maximizing the retention, infiltration, and purification of urban runoff by strengthening the application of green infrastructures based on the existing gray infrastructures, facilitating the promotion of runoff reduction and waterlogging prevention. The “green–gray” concept has become an effective method for solving the problem of WWDP. …”
Section: Introductionmentioning
confidence: 99%